Responsibility And Activity Of The Student In The Educational Process - Dosmatova, Dilnoza (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article comprehensively covers the issue of responsibility and activity of the student in the educational process. It is scientifically substantiated that the student’s conscious approach to educational activities, independent thinking and active participation in the educational process directly affect his level of knowledge and professional training. Also, effective methods of increasing student activity based on modern pedagogical approaches are analyzed.